Appointment Process, Functions and Reporting Lines with Regard to the General Secretariat and Operations Office (Tufts Archival Research Center, 2005)
The purpose of this note is to define functions, responsibilities and specify reporting lines for key positions in the Southern Sudan Referendum Commission General Secretariat, namely the Secretary-General, Deputy, Chief Referendum Operations Officer and Deputy CROO.